Analisis Dampak Proyek Pembangunan Pelabuhan Internasional Kijing Mempawah terhadap Lingkungan dan Sosial-Ekonomi Masyarakat - Syawaludin, Muhammad; Alfiyani, Nur (Jurnal Ekologi, Masyarakat dan Sains, 2025)
The Kijing International Port development project is expected to increase the potential for trade, logistics and maritime connectivity in Indonesia, especially in the West Kalimantan region. However, in the process of building and operating the port, various impacts were felt due to the lack of impact analysis and evaluation from PT Pelindo as the development manager. The purpose of this study is to analyze how the environmental and socio-economic impacts of the surrounding community as a result of the Kijing International Port development project. This research, which uses a descriptive qualitative approach, manages primary and secondary data by observing and analyzing the environmental hue in the development project area and obtaining additional data from theory, historical report records and other published information. The results found in this study are the emergence of negative impacts on the environment as a result of the development such as a decrease in air and sea water quality, an increase in water overflows and an increase in hazardous waste and garbage. Then this development project also has a positive impact on the socio-economy of the surrounding community in the form of increased employment opportunities, business opportunities and income for the local community.